1998
DOI: 10.1007/pl00006346
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Transposable Elements in the Heterochromatin and on the Y Chromosome of Drosophila simulans and Drosophila melanogaster

Abstract: The elements of the transposon families G, copia, mdg 1, 412, and gypsy that are located in the heterochromatin and on the Y chromosome have been identified by the Southern blotting technique in Drosophila simulans and D. melanogaster populations. Within species, the abundance of such elements differs between transposon families. Between species, the abundance in the heterochromatin and on the Y chromosome of the elements of the same family can differ greatly suggesting that differences within a species are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…The restriction of this transposition to the male germline should lead to there being more 412 insertions on the Y chromosome, and fewer on the X chromosome than on the autosomes, because the male is hemizygous in Drosophila. This is consistent with the observation that both D. simulans and D. melanogaster show numerous insertions of 412 and copia retrotransposons on the Y chromosome (Junakovic et al, 1997) with many times fewer insertions on the X chromosome than on the autosomes (Biémont, 1992;Biémont et al, 1997).…”
Section: Is Expressed Only In Malessupporting
confidence: 88%
“…The restriction of this transposition to the male germline should lead to there being more 412 insertions on the Y chromosome, and fewer on the X chromosome than on the autosomes, because the male is hemizygous in Drosophila. This is consistent with the observation that both D. simulans and D. melanogaster show numerous insertions of 412 and copia retrotransposons on the Y chromosome (Junakovic et al, 1997) with many times fewer insertions on the X chromosome than on the autosomes (Biémont, 1992;Biémont et al, 1997).…”
Section: Is Expressed Only In Malessupporting
confidence: 88%
“…It has been shown that each retrotransposon tends to have a different ratio of distribution between euchromatin and heterochromatin (12) and that different locations in the chromosome influence the conservation and the copy number of transposable elements (26,29). The elements tend to be more abundant in heterochromatin because of the lower density of functional genes in this region (13,26,29), but they are more degenerate and expressed at lower levels than elements present in the euchromatin (26). It is tempting to hypothesize that the high-copynumber retrotransposons present in the S. mansoni genome are preferentially located in heterochromatin, generating several truncated copies that would be inactive, thus accounting for their low transcriptional activity.…”
Section: Vol 78 2004mentioning
confidence: 99%
“…The endogenous retrovirus gypsy of Drosophila has potentially active elements that are predominantly located on the Y chromosome (12,20,34). However, the high numbers of gypsy elements on the Y chromosome are not due to preferences of integration but instead result from the loss of gypsy elements from the other chromosomes.…”
Section: Discussionmentioning
confidence: 99%